Surface Treatment of Polylactic Acid Fiber by Starch Nanocrystals and Interface Modification of Polylactic Acid Fiber-Reinforced Starch Composites - Zhou, Xiaodong; Sun, Ming; Ma, Huihuang; Yang, Shaoxia; Chen, Yingxuan; Liu, Haiyan (Journal of Composites and Biodegradable Polymers, 2022)
The surface of polylactic acid fiber (PLAF) was treated with self - manufactured starch nanocrystals (SNCs) to improve its interfacial adhesion with the starch matrix. Determination of optimum dispersion conditions of SNCs dispersion by transmittance. The effects of direct oscillatory deposition, chemical grafting SNCs modification, and SNCs dispersion concentration on the surface treatment effect of PLAF and its interfacial bonding with starch matrix were investigated. The results showed that the SNCs were successfully introduced into the PLAF surface, moreover, the modifying effect of the chemical grafted SNCs was better than the direct oscillatory deposition, the distribution of SNCs particles was more uniform on the fiber surface, strong chemical bonding to the fiber surface, make up for the surface damage of the fibers caused by aminolysis. At the SNCs dispersion concentration of 10 g/L, the PLAF tensile strength could be maintained at 582 MPa, a large amount of starch was evenly attached to the surface after pulling out. It showed that a strong interface bond with the starch matrix, the highest IFSS value was 2.57 MPa and the increase was by about 63 %. Therefore, the introduction of SNCs for interfacial modification of PLAF is of great significance and deserves further exploration.